9 - Réformes éducatives et développement en Afrique subsaharienne: Pour une vision partagée: by Medjomo Coulibaly - Medjomo Coulibaly (Africa Development, 1994)
Over the past decades, considerable efforts have been devoted by African governments to the establishment of educational institutions. As a result, schools for various training and purposes are being built and enrolment figures have sprung. Yet the educational enterprise has still not been fully rewarding. In an attempt to improve the system, a new reform agenda inspired and led by international donor agencies is in process. The author of this paper is looking at the actions initiated, the degree of responsiveness of the educational enterprise to these actions and the internal and external factors likely to influence the implementation process. He also looks at the policy requirements as well as policy instruments and implications necessary for these actions to succeed.